The relationship between critical reading interest and LMS learning using the CRIS (critical reading intention scale) instrument - Otang Kurniaman; Hadriana; Nur Islami; Zetra Hainul Putra; Zufriady; Garda Fathan Nuzulah; Radini (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This study aims to determine the relationship between critical reading interest and Learning Management System (LMS) learning using the Critical Reading Intention Scale (CRIS) instrument and its effect on student learning outcomes. Along with technological development in education, LMS has become an increasingly used platform for learning, but its relationship to students' critical reading interests has not been widely explored. The data used in this study were taken from various related journals, using the Critical Reading Intention Scale (CRIS) instrument to measure students' critical reading interest and questionnaires to identify LMS usage patterns and test questions to determine student learning outcomes. Through descriptive and quantitative descriptive analysis, the study results showed a significant positive relationship between students' critical reading interest and LMS learning using the Critical Reading Intention Scale (CRIS) instrument. After being given test questions, it was found that students with high reading interest got high learning outcomes and vice versa; students with low reading interest got low learning outcomes.